2020
DOI: 10.1177/0269881120916122
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of the self-reported Glasgow Antipsychotic Side-effect Scale using the clinician-rated UKU side-effect scale as gold standard reference

Abstract: Background: Antipsychotics are key for the treatment of psychotic and several non-psychotic disorders. Unfortunately, antipsychotic medications are associated with side effects, which may reduce quality of life and treatment adherence. Therefore, regular screening of antipsychotic side effects is essential. The Glasgow Antipsychotic Side-effect Scale is a patient self-report scale developed for this purpose. However, the Glasgow Antipsychotic Side-effect Scale has only been validated against another self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
(64 reference statements)
1
15
0
Order By: Relevance
“…The pharmacists assessed residents’ antipsychotic medicines using the GASS 19 and two of the residents reported a score of 22–42 (moderate side effects), while 89 residents reported a score under 21 (absent/mild side effects). None of the residents reported a score of 43–63 (severe side effects).…”
Section: Resultsmentioning
confidence: 99%
“…The pharmacists assessed residents’ antipsychotic medicines using the GASS 19 and two of the residents reported a score of 22–42 (moderate side effects), while 89 residents reported a score under 21 (absent/mild side effects). None of the residents reported a score of 43–63 (severe side effects).…”
Section: Resultsmentioning
confidence: 99%
“…Such a questionnaire would enable frequent and systematic screening for side effects that could be followed up by targeted side effect assessments by clinicians informed by the patients’ self-report and supplemented with relevant paraclinical tests, for example, electrocardiogram to screen for QTc prolongation. This objective, along with its underlying rationale, stems from our findings from the analogue clinical validation study of the GASS (Waddell and Taylor, 2008) among outpatients with psychotic disorders (Schouby Bock et al, 2020). In that study, we found that 48% of the participants had side effects according to the UKU that were not covered by the GASS (Schouby Bock et al, 2020), likely due to the fact that the GASS only covers 26 of the 48 UKU items.…”
Section: Discussionmentioning
confidence: 99%
“…This objective, along with its underlying rationale, stems from our findings from the analogue clinical validation study of the GASS (Waddell and Taylor, 2008) among outpatients with psychotic disorders (Schouby Bock et al, 2020). In that study, we found that 48% of the participants had side effects according to the UKU that were not covered by the GASS (Schouby Bock et al, 2020), likely due to the fact that the GASS only covers 26 of the 48 UKU items. Consequently, it fails to adequately assess psychiatric/cognitive (depression, concentration difficulties, failing memory, tension, sleep disturbances, emotional indifference, and increased dream activity), autonomic (diarrhea, constipation, and increased tendency to sweating), cutaneous (rash, pruritus, photosensitivity, and increased pigmentation), neurological (rigidity, epileptic seizures, and paresthesia), and other (headache, weight loss, and psychic and physical dependence) side effect domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization has identified BD as one of the most frequent causes of disability in youth [2]. The existing literature suggests that measurement-based care may be an effective clinical strategy in most psychiatric disorders [3][4][5][6], and monitoring of the clinical course of BD is therefore of high clinical and research interest. Several organizations, such as the International Society for Bipolar Disorders, have recommended the implementation of measurement-based care in the treatment of BD [7].…”
Section: Introductionmentioning
confidence: 99%